(untitled) (Tábano, 2025)
This paper reflects on the humanities. Among other things, it considers their current situation and the need to rethink their social role, as well as some challenges for the future. The impact of the working conditions of humanists on the results obtained as well as on the determination of their role in relation to society is addressed. Finally, the need to reestablish some of the basic characteristics of the humanities, such as the critical attitude of challenging the status quo, is analyzed.